Effect of Spacing, Planting Methods and Nitrogen on Maize Grain Yield - Fornah, Alimamy; Aula, Lawrence; Omara, Peter; Oyebiyi, Fikayo; Dhillon, Jagmandeep; Raun, William R. (Communications in Soil Science and Plant Analysis, 2020)
Maize (Zea mays L.) production in the developing countries takes place on marginal landscapes using indigenous planting methods that conflict with appropriate row spacing (RS) and plant to plant spacing (PPS). A study was conducted to determine the effect of different RS, variable plant densities and different planting methods on maize grain yield. This study was conducted for two years at three locations in Oklahoma including Lake Carl Blackwell (Port silt loam), Efaw (Ashport silty clay loam), and Perkins (Teller sandy loam-fine-loamy). Fourteen treatments were evaluated at each location in a randomized complete block design with three replications. Treatments included two RS (0.51 m, 0.76 m), three nitrogen (N) application rates (0, 60, 120 kg N ha−1), two PPS (0.15 m, 0.30 m) and two planting methods (Greenseeder hand planter; farmers practice). Results showed an increase in grain yield by 34% in 2017 and 44% in 2018 for the narrow RS of 0.51 m compared to the 0.76 m RS. This was likely due to increased plant population at the narrow RS. This study suggests that maize producers in developing countries could use narrow RS (0.51 m) with wide PPS (0.30 m) to increase grain yields.
Keywords: Maize Grain Yield; Row spacing; Plant spacing; Nitrogen rate; Maize planter